2021
DOI: 10.1071/cp20275
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of seed yield and oil nutritional attributes in linseed dominated by biennial variation

Abstract: Improving seed yield and oil quality of oilseed crops can aid in provision of a nutritious diet for humans. A worldwide collection of linseed was evaluated for seed yield (YLD), seed oil (OIL) and protein content (PRO), oil fatty acid composition, omega-3 to omega-6 ratio (ω3/ω6), total tocopherol content (TTC), and total phenolic content (TPC). At 2 years, higher temperature (~7%) and lower relative humidity (~16.6%) during the seed filling and maturity period (dryer condition) were correlated with significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…Depending on the cultivation site, our results showed an oil content between 47.2% (SPG) and 45.2% (ALB), and PUFAs between 72% (SPG) and 70% (ALB), close to or higher than those previously reported in Mediterranean areas [33,49]. It is known that the FA profile is strongly related to genetic characteristics [58]; in the present study a great variability among the tested varieties was observed, confirming this statement. Alfa-linolenic acid was the most abundant FA in all the varieties, but Libra exhibited the highest level (around 61%).…”
Section: Discussionsupporting
confidence: 89%
“…Depending on the cultivation site, our results showed an oil content between 47.2% (SPG) and 45.2% (ALB), and PUFAs between 72% (SPG) and 70% (ALB), close to or higher than those previously reported in Mediterranean areas [33,49]. It is known that the FA profile is strongly related to genetic characteristics [58]; in the present study a great variability among the tested varieties was observed, confirming this statement. Alfa-linolenic acid was the most abundant FA in all the varieties, but Libra exhibited the highest level (around 61%).…”
Section: Discussionsupporting
confidence: 89%